Introduction to rubrics : an assessment tool to save grading time, convey effective feedback, and promote student learning - Stevens, Dannelle D.; Levi, Antonia, 1947- (Sterling, Virginia Stylus, 2005)
-back cover.
"This book defines what rubrics are, and how to construct and use them. It provides a complete introduction for anyone starting out to integrate rubrics into their teaching."
Includes bibliographical references (p. 111-112) and index.
Keywords: Whitman College -- Center for Teaching and Learning collection; Grading and marking (Students); Students -- Rating of